2011
DOI: 10.1371/journal.pone.0022275
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Phylogeny to Interpret Cross-Cultural Patterns in Plant Use and Guide Medicinal Plant Discovery: An Example from Pterocarpus (Leguminosae)

Abstract: BackgroundThe study of traditional knowledge of medicinal plants has led to discoveries that have helped combat diseases and improve healthcare. However, the development of quantitative measures that can assist our quest for new medicinal plants has not greatly advanced in recent years. Phylogenetic tools have entered many scientific fields in the last two decades to provide explanatory power, but have been overlooked in ethnomedicinal studies. Several studies show that medicinal properties are not randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 100 publications
11
117
0
4
Order By: Relevance
“…f. (Mackinder & Pennington, 2011); American Vigna (Delgado-Salinas & al., 2011); Pterocarpus Jacq. (Saslis-Lagoudakis & al., 2011); Anthyllis L. (Degtjareva & al., 2012); and Crotalaria L. . In addition, there have been recent higher-level studies of generic groups or clades, such as the resin-producing Detarieae (Fougère- Danezan & al., 2007Danezan & al., , 2010, Acacia and allies (Brown & al., 2008;Murphy & al., 2010;, Swartzia and allies (Torke & Schaal, 2008), phaseoloid legumes (Stefanović & al., 2009), Lonchocarpus and allies (Silva & al., 2012); tribes such as Hedysareae (Ahangarian & al., 2007), Crotalarieae (Boatwright & al., 2008a), Podalyrieae (Boatwright & al., 2008b), and Indigofereae (Schrire & al., 2009).…”
Section: Integrating Morphologymentioning
confidence: 99%
“…f. (Mackinder & Pennington, 2011); American Vigna (Delgado-Salinas & al., 2011); Pterocarpus Jacq. (Saslis-Lagoudakis & al., 2011); Anthyllis L. (Degtjareva & al., 2012); and Crotalaria L. . In addition, there have been recent higher-level studies of generic groups or clades, such as the resin-producing Detarieae (Fougère- Danezan & al., 2007Danezan & al., , 2010, Acacia and allies (Brown & al., 2008;Murphy & al., 2010;, Swartzia and allies (Torke & Schaal, 2008), phaseoloid legumes (Stefanović & al., 2009), Lonchocarpus and allies (Silva & al., 2012); tribes such as Hedysareae (Ahangarian & al., 2007), Crotalarieae (Boatwright & al., 2008a), Podalyrieae (Boatwright & al., 2008b), and Indigofereae (Schrire & al., 2009).…”
Section: Integrating Morphologymentioning
confidence: 99%
“…It is suggested that evolutionary history might better capture functional diversity including unmeasured or hard-to-measure traits (Crozier 1997 ;Faith 2002 ). As such, phylogeny provides a unique framework that captures both known (Forest et al 2007 ;Saslis-Lagoudakis et al 2011 ) and unknown ecosystem services (Faith et al 2010 ). Understanding how the current extinction crisis will prune the tree-of-life is therefore critical for ensuring a continued provisioning of the ecosystem services upon which we rely, but for which we might lack detailed ecological knowledge of underlying process or mechanism (Faith et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…), Orchidaceae (22,000 spp. ), and other large plant families: (1) Fabaceae includes many useful plants such as crops, vegetables, timber, ornamentals and medicinal plants ( Van der Maesen & Somaatmadja, 1992;Gepts & al., 2005;Brink & Belay, 2006;Saslis-Lagoudakis, 2011); (2) Habitat diversity of Fabaceae is extremely high; legumes occur from tropics to arctic zones, from the seashore to alpine habitats, and in rain forests, mangroves, peat swamp forests, seasonal forests, savannas, and deserts (e.g., Prado, 1993;Prado & Gibbs, 1993;Pennington & al., 2000;Prado, 2000). In addition, Fabaceae show high diversity in all of three main tropical vegetation types including tropical rain forests, dry forests and woody savannas (Sheil, 2003;Ter Steege & al., 2006;Sarkinen & al., 2011), while other families have comparable diversity, if at all, in just one of these vegetation types; (3) Plants of Fabaceae harbor many specific herbivorous insects and support characteristic food webs (Southgate, 1979;Harmon & al., 2009); (4) Many legume species are symbiotic with nodule-forming bacteria with nitrogen fixation ability, and as such support important ecosystem functions (Sprent, 2009); (5) Fabaceae includes many invasive species, presenting serious economic threats and costs (Bradshaw & al., 2008); (6) Fabaceae harbors extremely diversified life forms, including annuals, shrubs, canopy trees, vines, and aquatic plants ( Lewis & al., 2005); (7) Fabaceae are highly diversified in functional traits of leaves, stems, flowers, fruits and seeds (Lewis & al., 2005;Kleyer & al., 2008;Kattge & al., 2011a, b); (8) Fabaceae display a range of rarity, from extreme endemics only known from small local areas, which are exceedingly vulnerable to threats (Raimondo & al., 2009), to widespread and even cosmopolitan species; (9) Flowers of Fabaceae are generally animal-pollinated and thus sensitive to pollinator loss (Proctor & al., 1996); (10) Fabaceae contains many unique chemicals, especially in the seeds, for which a rich database is available (Bisby, 1994;Dixon & Sumner, 2003); (11) Legume taxonomy and phylogeny is well-studied by an active global legume systematics research community that resulted in the ten volumes of the Advances in Legume Systematics series, and (12) Whole-genome sequences of four species of Fab aceae, Medicago truncatula Gaertn.…”
Section: Introductionmentioning
confidence: 99%